2021
DOI: 10.3390/cells10123294
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Toxicity of Disulfiram in Preclinical Models of Nephropathic Cystinosis

Abstract: Nephropathic cystinosis is a rare disease caused by mutations of the CTNS gene that encodes for cystinosin, a lysosomal cystine/H+ symporter. The disease is characterized by early-onset chronic kidney failure and progressive development of extra-renal complications related to cystine accumulation in all tissues. At the cellular level, several alterations have been demonstrated, including enhanced apoptosis, altered autophagy, defective intracellular trafficking, and cell oxidation, among others. Current therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…( 27 ). The renal Fanconi syndrome was significantly milder, compared with that of previous reports ( 28 ); however, the causes of this discrepancy are currently under investigation in our laboratory. This cystinotic mouse model has been widely used to obtain key insights in the pathophysiology of cystinosis ( 9 , 26 , 29–32 ) and to develop new therapeutic strategies ( 30 , 33–35 ).…”
Section: Discussioncontrasting
confidence: 65%
“…( 27 ). The renal Fanconi syndrome was significantly milder, compared with that of previous reports ( 28 ); however, the causes of this discrepancy are currently under investigation in our laboratory. This cystinotic mouse model has been widely used to obtain key insights in the pathophysiology of cystinosis ( 9 , 26 , 29–32 ) and to develop new therapeutic strategies ( 30 , 33–35 ).…”
Section: Discussioncontrasting
confidence: 65%
“…They produced a list of additional potential drugs acting with the exact mechanisms of action. In a follow-up paper, the same authors investigated the effects of DSF on animal models using mice and zebrafish [ 25 ]. Notwithstanding the decades of DSF application, in particular, to treat chronic alcoholism, prolonged exposure to the drug resulted in markedly increased toxicity for cystinotic animals.…”
Section: Shooting At Random: the Valuable Results Of High-throughput ...mentioning
confidence: 99%
“…A workflow detailing the entire process is visible in Figure 1 , and papers are synthesized in Table 1 . Searching for these articles’ DOIs on UniProt returned two hits [ 24 , 25 ] linked to proteins not associated with any OMIM or OrphaNet on UniProtKB, while searching the publication DOIs on OMIM using the “ref_doi’’ key yielded no results. Furthermore, ~30% of the articles were not associated with any LSD-related Medical Subject Headings (MeSHs), and only five of those 27 documents were annotated on PubMed with the Drug Repositioning MeSH.…”
Section: Drug Repositioning For Lysosomal Storage Disorders: Still a ...mentioning
confidence: 99%
“…Diffusion through lysosomal membranes is typically restricted to molecules of mass less than 200-230 daltons [31]. Also, Taranta et al [30] reported the cystine-depleting and anti-apoptotic properties of the disulfide, disulfiram, confirmed by secondary in vitro assays and after treating Ctns-/-mice with 200 mg/kg/day of disulfiram for 3 months. However, at this dosage, growth impairment was observed and long-term treatment with a lower dose (100 mg/kg/day) did not inhibit growth, but failed to reduce cystine accumulation, caused premature death, and did not prevent the development of renal lesions.…”
Section: Discussionmentioning
confidence: 99%